16 because if she wants to do it in a 8 hour work day she’d make $72 and make 16 deliveries and have two extra dollars
Answer:
$21,623.70
Step-by-step explanation:
A suitable financial calculator can compute the beginning balance and the remaining balance for you. The attachments show a TI-Nspire calculator's TVM solver app being used to answer this question.
The first attachment shows the computation of the loan value. It is about $37,624.54.
The second attachment shows the computation of the remaining balance after 16 of the 32 semi-annual payments have been made.
The loan balance 8 years from the end of the loan will be about $21,623.70.
Answer:
x = 17, MN = 11
Step-by-step explanation:
Given 2 secants from an external point to a circle, then
The product of the external part and the whole of one secant is equal to the product of the external part and the whole of the other secant.
(5)
7(7 + x) = 8(8 + 13) = 8 × 21 = 168 ( divide both sides by 7 )
7 + x = 24 ( subtract 7 from both sides )
x = 17
(6)
9(9 + 2x - 7) = 10(10 + 8)
9(2x + 2) = 10 × 18 = 180 ( divide both sides by 9 )
2x + 2 = 20 ( subtract 2 from both sides )
2x = 18 ( divide both sides by 2 )
x = 9
Then
MN = 2x - 7 = 2(9) - 7 = 18 - 7 = 11
By algebra properties we find the following relationships between each pair of algebraic expressions:
- First equation: Case 4
- Second equation: Case 1
- Third equation: Case 2
- Fourth equation: Case 5
- Fifth equation: Case 3
<h3>How to determine pairs of equivalent equations</h3>
In this we must determine the equivalent algebraic expression related to given expressions, this can be done by applying algebra properties on equations from the second column until equivalent expression is found. Now we proceed to find for each case:
First equation
(7 - 2 · x) + (3 · x - 11)
(7 - 11) + (- 2 · x + 3 · x)
- 4 + (- 2 + 3) · x
- 4 + (1) · x
- 4 + (5 - 4) · x
- 4 - 4 · x + 5 · x
- 4 · (x + 1) + 5 · x → Case 4
Second equation
- 7 + 6 · x - 4 · x + 3
(6 · x - 4 · x) + (- 7 + 3)
(6 - 4) · x - 4
2 · x - 4
2 · (x - 2) → Case 1
Third equation
9 · x - 2 · (3 · x - 3)
9 · x - 6 · x + 6
3 · x + 6
(2 + 1) · x + (14 - 8)
[1 - (- 2)] · x + (14 - 8)
(x + 14) - (8 - 2 · x) → Case 2
Fourth equation
- 3 · x + 6 + 4 · x
x + 6
(5 - 4) · x + (7 - 1)
(7 + 5 · x) + (- 4 · x - 1) → Case 5
Fifth equation
- 2 · x + 9 + 5 · x + 6
3 · x + 15
3 · (x + 5) → Case 3
To learn more on algebraic equations: brainly.com/question/24875240
#SPJ1
X= 10
This is because 180-95= 85 which would make 8x+5= 85
Subtract 5 from both sides and get 8x=80
Then, divide 8 from both sides and get x=10